Get real and get in : how to get into the college of your dreams by being your authentic self - Legatt, Aviva (St. Martin's Griffin, 2021)
"An insider's college admissions guide that teaches students to identify and harness their unique passions, stand out from the crowd, and achieve their dreams. Getting into the right college has never been tougher. Competitive programs are admitting fewer and fewer students each year, while the Common Application has made it easy to apply to 30-40 schools in a single admissions cycle. Gen Y and Z workers are having trouble finding rewarding careers after graduating, and in the wake of the college admissions scandal, many are questioning if an ethical pathway into top-tier schools even exists. The struggle is real. Yet most college applicants still follow the traditional wisdom on getting in, like "have a perfect SAT score" or "become the president of ten clubs." Dr. Aviva Legatt has spent her career in higher education as a professor, counselor, and admissions officer in the Ivy League, and she wants to let students in on a secret: admissions boards are sick of seeing the same cookie-cutter applications. What were once considered best practices for "doing high school right" are now so commonplace that they have become a liability. Get Real and Get In rejects these obsolete methods, teaching readers to think outside of the box and focus on what admissions officers are really looking for-young people who dare to be their most authentic selves. Through engaging, accessible, and empathetic prose, this book forms an inspirational roadmap for readers to uncover their true passions and leverage them to create applications that truly stand out from the crowd. It also features a variety of useful exercises and candid stories from many influential figures from diverse backgrounds and careers, which teach students to look beyond just getting into a "good" college and focus more actively on identifying and attaining their long-range goals. Get Real and Get In is designed to ignite an essential mindset shift in students: stop trying to just "get in" and start figuring out exactly what you want from life and how to get it. Stop managing the impressions you make on admissions officers and start defying impressions. This is an essential guide to cutting through the noise of the admissions process and gaining the confidence to forge one's own path to success-in college and beyond"--